2019
DOI: 10.1097/wnp.0000000000000655
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Spindle Features and Neurobehavioral Performance in Healthy School-Aged Children

Abstract: Purpose: In adults, central fast-frequency sleep spindles are involved in learning and memory functions. The density of local spindles is higher than global spindles, emphasizing the importance of local plastic neural processes. In children, findings on the association of spindles with cognition are more variable. Hence, we aim to study whether the local spindles are also important for neurobehavioral performance in children. Methods: We studied the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In a similar examination, Sulkamo et al. (2021) investigated 9‐year olds and found a positive correlation between central spindle density and the object assembly domain of the WISC, but not with overall IQ. Hoedlmoser et al.…”
Section: Neurophysiology Of Sleep Spindlesmentioning
confidence: 97%
See 4 more Smart Citations
“…In a similar examination, Sulkamo et al. (2021) investigated 9‐year olds and found a positive correlation between central spindle density and the object assembly domain of the WISC, but not with overall IQ. Hoedlmoser et al.…”
Section: Neurophysiology Of Sleep Spindlesmentioning
confidence: 97%
“…The reviewed studies also highlight some different relations among spindle features and memory performance on a task compared to memory assessed as a domain on the Neuropsychological Developmental Assessment (Brooks et al, 2009) in children around 9 years of age. In one study, Sulkamo et al (2021) found that central spindle frequency was positively associated with speeded naming, and faster central spindles were associated with poorer performance for facial memory; however, spindles were not associated with narrative memory. Contrary to these findings, Chatburn et al (2013) found that faster spindle frequencies were positively correlated with narrative memory.…”
Section: Memorymentioning
confidence: 99%
See 3 more Smart Citations